Anion receptors with 1, 3, 5‐triazacyclohexane and 1, 4, 7, 10‐tetraazacyclododecane scaffolds. (7th July 2020) - Valadbeigi, Yaser; Ilbeigi, Vahideh; Valadbeigi, Younes
Abstract: Fluoride, chloride, and bromide affinities of 1, 3, 5‐triazacyclohexane (TACH) and 1, 4, 7, 10‐tetraazacyclododecane (Cyclen) were studied theoretically using ωB97XD and B3LYP functionals and 6‐311++G(d, p) basis set. To enhance and modify the anion affinities of TACH and Cyclen, several anion receptors with –(CH2 )n OH and –(CH2 )n NH2 ( n = 1–3) substituents were designed and investigated. These anion receptors are attached to the halides (X − ) via formation of NH … X and OH … X hydrogen bonds. The anion affinities calculated by ωB97XD were larger than those obtained by B3LYP indicating the dispersion contribution to the anion affinities. It was found that the anion affinities of these compounds depend on both the alkyl chain length and nature of the interaction, NH … X or OH … X. The ωB97XD‐calculated fluoride affinities of TACH and Cyclen were 149.5 and 207.2 kJ mol −1, respectively. By substitution of –(CH2 )n OH groups, anion receptors with F − affinities of 277 and 326 kJ mol −1 were obtained, which can be classified among the strongest organic anion receptors. The affinity of all TACH and Cyclen toward the halides was as F − > Cl − > Br −, while substitution of –(CH2 )3 OH and –(CH2 )3 NH2 into Cyclen changed the trend to F − > Br − > Cl − . Abstract : Cyclen with four NH groups can act as an anion receptor via formation of hydrogen bonds with the anion. Substitution of –(CH2 )n OH into Cyclen enhances its anion affinity and changes its affinity toward different halides.